1986
DOI: 10.1038/ki.1986.96
|View full text |Cite
|
Sign up to set email alerts
|

Role of the loop segment in the urinary concentrating defect of hypercalcemia

Abstract: Hypercalcemia is associated with impaired urinary concentrating ability. To explore the mechanism(s) by which hypercalcemia impairs chloride transport in the loop of Henle, we carried out in vivo microperfusion of the loop segment in Sprague-Dawley rats rendered acutely hypercalcemic (12.1 +/- 0.1 mg/dliter) by calcium gluconate infusion. Control rats were infused with sodium gluconate and had normal plasma calcium (8.0 +/- 0.2 mg/dliter). Compared to control, fractional chloride reabsorption was decreased (61… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
1

Year Published

1993
1993
2014
2014

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 22 publications
0
4
1
Order By: Relevance
“…This is in clear contrast to other loop segment studies where J. was 2 50% of the perfused rate (18,28 ( 14,20). Specificity offurosemide.…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…This is in clear contrast to other loop segment studies where J. was 2 50% of the perfused rate (18,28 ( 14,20). Specificity offurosemide.…”
Section: Discussioncontrasting
confidence: 53%
“…There is evidence from in vitro studies that acute increases in extracellular [Ca2+] can directly inhibit AVP stimulated production of cAMP and thus could mediate the transport defect ( 17 ). In acute hypercalcemia, loop Cl reabsorption is decreased by an indomethacin-resistant mechanism ( 18). However, two previous studies have shown that renal PGE2 excretion is strikingly elevated in rats with chronic hypercalcemia ( 15,19).…”
Section: Introductionmentioning
confidence: 84%
“…IT IS WELL KNOWN THAT HYPERCALCEMIA in both humans and experimental animals is associated with a urinary concentrating defect and significant polyuria (11,20,30). Despite considerable experimental work (2,3,10), the precise pathogenic mechanisms involved in the impaired urinary concentration remains only partly understood and it is likely to be multifactorial. Several lines of evidence have pointed to a significant defect in countercurrent multiplication in hypercalcemia, which is associated with decreased medullary hypertonicity (2,28,29) and to a defect in collecting duct water reabsorption.…”
mentioning
confidence: 99%
“…Alterations in hormone levels, especially arginine vasopressin (AVP) release or response (4), renal hemodynamics (8), and renal tubular function (19) have been examined as possible mediators of the defect. However, the pathogenic mechanisms involved in the impaired urinary concentration are likely to be multifactorial.…”
mentioning
confidence: 99%